Transformational Leadership and Organizational Health: Building Quality Management and Accreditation Excellence in Private Universities - Arip Amin; Diding Nurdin; Suryadi Suryadi; Uum Murfiah; Tyagita Ayuningtyas (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study explores the influence of transformational leadership on organizational health and its implications for institutional accreditation quality management in private universities (PTS). In the context of global competition and the Fourth Industrial Revolution, leadership and organizational quality are crucial for higher education sustainability. A mixed-methods approach was employed, integrating quantitative data from structured questionnaires with qualitative insights through interviews. Respondents included lecturers and academic staff from private universities in West Java and Banten. Data analysis was conducted using Structural Equation Modeling (SEM) via SmartPLS to evaluate the relationships among variables. The findings demonstrate that transformational leadership significantly and positively influences both organizational health and the quality management of institutional accreditation. Key leadership dimensions—idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration—are instrumental in shaping a healthy academic environment. Moreover, organizational health acts as a mediating variable, enhancing the impact of leadership on accreditation outcomes through improved internal alignment, strategy execution, and organizational renewal. This study highlights the strategic role of transformational leadership in strengthening institutional quality frameworks. The integration of leadership and organizational health offers a practical paradigm for accreditation excellence. The findings are particularly relevant for resource-constrained private universities seeking competitive positioning in a globalized education landscape. Transformational leadership, supported by a healthy organizational environment, plays a critical role in advancing accreditation quality management in private universities. These insights offer theoretical and practical contributions to higher education leadership and quality assurance.